2001
DOI: 10.1046/j.0962-1075.2001.00289.x
|View full text |Cite
|
Sign up to set email alerts
|

The thymidylate synthase gene of Hz‐1 virus: A gene captured from its lepidopteran host

Abstract: The sequence analysis of a thymidylate synthase gene was identified in the Hz-1 virus HindIII-D fragment. The viral thymidylate synthase gene encodes a protein of 295 amino acids, and is closely related to that of insect, mammals and herpesvirus. The thymidylate synthase gene identified was a genuine viral gene in that it was only detected in cells infected with Hz-1 virus but not in the mock infected cells, by Southern blot analysis and by RT-PCR. Results of phylogenetic analysis based on non-synonymous and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, taxon distributions and phylogenetic analysis of six genes, apoptosis protein inhibitor, dihydrofolate reductase, glycine hydroxymethyltransferase, thymidylate synthase, triacylglycerol lipase and UDP‐glucosyltransferase, indicated that they were transferred from Lepidoptera to lepidopteran viruses. These lepidopteran–viral HGTs have been previously reported (Chen et al ., ; Hughes & Friedman, ; Wu & Zhang, ). We did not pursue further analysis of these HGTs but rather limited our efforts to the study of the effect of HGT on the Lepidoptera.…”
Section: Resultsmentioning
confidence: 99%
“…However, taxon distributions and phylogenetic analysis of six genes, apoptosis protein inhibitor, dihydrofolate reductase, glycine hydroxymethyltransferase, thymidylate synthase, triacylglycerol lipase and UDP‐glucosyltransferase, indicated that they were transferred from Lepidoptera to lepidopteran viruses. These lepidopteran–viral HGTs have been previously reported (Chen et al ., ; Hughes & Friedman, ; Wu & Zhang, ). We did not pursue further analysis of these HGTs but rather limited our efforts to the study of the effect of HGT on the Lepidoptera.…”
Section: Resultsmentioning
confidence: 99%
“…TS is well conserved across species and is involved in the synthesis of dTMP precursors from dUTP [43,44]. Interestingly, all identified viral TS genes are thought to be acquired from their hosts in independent incidents rather than originating from a common ancestor [45,46]. …”
Section: Resultsmentioning
confidence: 99%
“…However, homologs of the ts gene have been identified in the genomes of two other insect viruses, Chilo iridescent virus (47) and Melanoplus sanguinipes entomopoxvirus (1). Our previous analysis suggested that the Hz-1 virus ts gene originated from its lepidopteran host and that the ts genes of Hz-1 virus, Chilo iridescent virus, and Melanoplus sanguinipes entomopoxvirus originated from independent recombination events (16).…”
Section: Resultsmentioning
confidence: 99%